Biogenic technology for recultivation of lands contaminated due to rocket propellant spillage. (April 2015) - Kovshov, S.V.; Garkushev, A.U.; Sazykin, A.M.
Abstract: This article describes the problem of soil properties deterioration due to rocket propellant spillage. Melange and samin are considered to be the main pollutants. Provision is made for assessment of the existing mechanisms for monitoring of quality and recultivation of lands disturbed by rocket propellant spills. Some major disadvantages of currently used standard recultivation technologies are listed. An alternative is the use of more environmentally safe and cost effective methods aimed at disturbed lands biological restoration. An example of such a technology is covering the affected area with a biogenic mixture consisting of biohumus and sodium carboxymethyl cellulose followed by seeding it with specially selected herbal mixtures. It was found out that the most rational parameters of such protective layer is its thickness of 3 cm, and 99:1 ratio of its constituent components. Highlights: Recultivation technology for lands contaminated by rocket propellant is suggested. Proposed method allows to drastically increase efficiency of recultivation. Bioproductive medium is being formed to facilitate creation of secondary ecosystems.